ARTHROPODS: HABITAT, FEATURES OF LIFE - MANISHA KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
Soil arthropods are a group of soil-inhabited arthropods belonging to the classes of Crustacea, Arachnida, Myriapoda, and Insecta. They are generally characterized by features, namely a hard chitinous exoskeleton, segmentation, multiple jointed appendages, and an open circulatory system. Orchards are complex ecosystems in which plants have adjacent associations with different living constituents. Consequently, the fundamental modification in the community of plants has an impact on the population of arthropods Mango and litchi are essential groups of fruit crops with highly nutritious value Farming, on the other hand, is considered to reduce the effects of conventional agricultural practices on the environment and especially halt the decline of biodiversity in the agricultural landscape